Dynamic Capabilities and Motivation for University Studies - Drouin, Nicolas (2020)
We present our results using an illustrative exemplary case of our work on the dynamic capabilities and the construction of a project within a student population enrolled in university courses. This period of life allows the transition between adolescence and adulthood, but also between a state of learner to that of worker inserted into the economic fabric of society. This identity construction is based on the social representations inherent to each group, but their integration at the individual level is influenced by the subjective experience of each person. Our results show that the sense of being competent, which is part of being engaged in a project, is influenced by emotional and experiential states. This influence can also be readjusted to better reflect a current self-image when there is a supported reflexive process.